Contesting Indonesia in children’s films: An analysis of language use and mise-en-scène - Noorman, Safrina; Nafisah, Nia (Universitas Pendidikan Indonesia, 2016)
This research aims to investigate and interpret nationalism in Indonesian films for children with local settings. Four films for children –Garuda Di Dadaku (2009), Di Timur Matahari (2011), Serdadu Kumbang (2011), dan Tanah Surga…katanya (2012)- are analyzed with reference to the theoretical assumption of film as a form system covering its language use and mise-en-scène (Bordwell Thomson, 2010). Employing a formal system analysis, aspects of nationalism were constructed and interpreted using Bhabha’s (2000) dissemination theory and a seminal theory of ideology in children and teenagers’ literary texts by Hollindale (1988). Results show that nationalism is presented: 1) through the films’ mise-en-scène which generates attachment to Indonesian nation; 2) in abstract notions through the films interconnection with aspects of humanity, social justice, and unity; 3) the use of children characters’ points of view. The presentation implied that, in the context of building nationalism, the constructed meanings from exposures on nationalism originated in local issues as well as socio-cultural issues have placed children in an instrumental role as the glue in the weaving of Indonesian nationalism. These findings generate three implications: (1) giving inputs about the kind of texts for children which focus on children’s point of view; (2) encouraging the exposure of localities to raise the sense of nationalism; and (3) preparing practical ways to empower film as part of national character building in teaching children.